An analysis of Cost X-efficiency and Determinants of Loan Loss Provision in China Commercial Banks - HUANG, SICHEN (2017)
This paper uses GMM estimator to analysis the determinants of loan loss provisioning for commercial banks in China. A sample of 55 commercial banks in China are used in a dynamic panel dataset from 2010 to 2016. Although many studies estimate discretionary provision determinants, we argue that it is also crucial to analyse non-discretionary determinants of LLPs. Therefore, apart from pro-cyclicality, income smoothing and capital management hypothesis we further investigate cost efficiency and bank insolvency (Z-score) as possible determinants of loan loss provisions. To do so we investigate cost efficiency by using Stochastic Frontier Approach, and a dynamic system GMM estimator is used for loan loss provision model. In this study, it is found that cost efficiency in loan loss provisions does exist in Chinese commercial banks; In the meantime, the LLPs are found to be pro-cyclical and the behaviour of capital management was also found. However, there is no evidence for the existence of income smoothing behaviour in Chinese banks, and the Z-score which measures insolvency risk is insignificant, thus, it cannot indicate any relationship between LLPs and insolvency risk.